Poland: An Attempt at a Balance Between the Protection of Family Holding and the Freedoms of the European Union - Ledwoń , Paulina (Acquisition of Agricultural Lands, 2022)
The aim of this article is to present the problem of acquisition (including cross-border acquisition) of agricultural real estates and agricultural holdings in the Republic of Poland, with particular emphasis on the issue of regulating the acquisition of agricultural real estates as an instrument for the protection of family farms. By analyzing current legislation, jurisprudence, and doctrine, the author tries to discern the key issues in the field of agricultural law. Starting from fundamental notions on which the whole article is based, such as real estate, agricultural real estate (land), agricultural holding, individual farmer, and family holding, the author proceeds to detail issues concerning the acquisition of ownership of agricultural land (holdings), including inheritance, acquisition of other rights on agricultural land, establishment of a bonding relation in the form of a lease of agricultural land, and acquisition of shares (stocks) in companies that own agricultural land. Next, the author presents the constitutional norm of the agricultural system of the Polish state and attempts to answer the question of whether the Commission proceedings have been initiated against Poland in connection with the breach of obligations. In conclusion, the author concludes that a considerable part of the issues taken up by the European Commission in the Interpretative Communication touches upon the Polish legal instruments of agricultural law. Keywords: agricultural land, agricultural real estate, agricultural holding, individual farmer, Act on Shaping of the Agricultural System, Act on Acquisition of Real Estate by Foreigners, Poland